"A new book in Jewish affairs begins": Maurice de Hirsch and the waning power of Jewish philanthropy at the Fin-de-Siècle. Issue 4 (2nd October 2018) - Lehmann, Matthias B.
ABSTRACT: This article looks at Jewish responses to the death of the banker, railroad entrepreneur, and philanthropist Maurice de Hirsch in 1896, the same year that Theodor Herzl published his Jewish State . Examining printed eulogies and obituaries that appeared in Jewish newspapers, from Eastern Europe to France, and from Germany to the Ottoman Empire, the article demonstrates how contemporaries understood the passing of Baron Hirsch as the end of a golden age of Jewish philanthropy. While they celebrated the legacy of the late benefactor, the leaders of Jewish public opinion across Europe realized that the challenges that began to undermine the liberal order established in the century of emancipation were calling for a political response that philanthropy could no longer offer.